Experimentation and innovation in police reform: Timor-Leste, Solomon Islands and Bougainville. (June 2015) - Dinnen, Sinclair; Peake, Gordon
The plural character of policing provision in most countries is now widely acknowledged, though rarely reflected in the practical police reform programming undertaken by donors. While much of the literature on international police assistance focuses on its modest results and innate limitations, less attention has been paid to those still relatively rare programmes that have sought to engage with the local realities of plural policing. This is particularly so in the conflict-affected and fragile settings where such assistance is typically provided. In this article, we present three case studies of policing innovation and experimentation from Timor-Leste, Solomon Islands and Bougainville, respectively, set in the context of the recent and very different post-conflict interventions in each place. While not wishing to overstate the impact of these modest programmes, we highlight their potential contribution to fostering productive relations across the multiple social orders and sources of authority found in many post-colonial, post-conflict and otherwise fragile contexts. We tentatively conclude that the most significant contribution of these kinds of initiative is likely to lie beyond the realm of institutionalised policing and, specifically, in relation to larger processes of social and political change, including state formation, under way in these places.